A STUDY OF LITERATURE: CRYPTOCURRENCY OF SYARIAH PERSPECTIVE - Fuadi, Fuadi; Afrizal, Afrizal; Shabri Abd. Majid, M; Marliyah, Marliyah; Handayani, Rita (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Cryptocurrency is a digital or virtual currency, which does not have a physical form like fiat money. This crypto currency can only be used through devices such as PCs, laptops, smartphones and other devices that are connected to the internet. There are several advantages in a crypto system that uses blockchain system, such as transaction security, convenience, speed and can be used across countries and continents, however cryptocurrency which is currently circulating also still have weaknesses, including there is no supervisory authority, even many countries have disagreements over the legality of this cryptocurrency. The debate about the pros and cons regarding to the use of cryptocurrency becomes dynamics among the experts including the scholars who have study from Islamic point of view. This research aims to examine the dynamics of using cryptocurrency from ushul fiqh point of view, where the methods which used in this research are al-qur'an, al-Hadith, Qiyas and Sad-Adzariyah. Basically the use of cryptocurrency is allowed to meet cetain conditions that is by removing batil elements as in Quran surah An-Nisa verse 29, those batil elements are gharar and mayshir. Moreover, cryptocurrency must also have clear legality in a country for security in their use.